Comparison of Surgical Outcomes of Laparoscopic Glue and Laparoscopic Suture Hernioplasty in Pediatric Female Inguinal Hernia - In Geol Ho; Kyong Ihn; Ho Jong Jeon; Yonghyun Na; Dongeun Lee; Seok Joo Han (MDPI AG, 2022)
This study aimed to report the surgical outcomes of laparoscopic glue hernioplasty (LGH) compared with conventional laparoscopic suture hernioplasty (LSH) in pediatric female inguinal hernia repair. We retrospectively analyzed 465 female pediatric patients who underwent laparoscopic inguinal hernia repair between January 2013 and December 2020. LGH and LSH were performed in 95 and 370 cases, respectively. Surgical outcomes (length of hospital stay, operative time, complications, and recurrences) were compared between the LGH and LSH groups. We found that the operation times for bilateral hernia repair were shorter in the LGH group (LGH: 35.5 ± 8.2 min, LSH: 45.2 ± 11.6 min; p < 0.001). No significant differences in complications or recurrences were observed between the two groups during the follow-up period. Our findings suggest that LGH is a feasible and easily applied surgical technique for the treatment of pediatric female inguinal hernia.